2021
DOI: 10.1155/2021/2344212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome Predictive Value of Procalcitonin in Patients Suspected with Infection in the Emergency Department

Abstract: Procalcitonin (PCT) may be useful for early risk stratification in the emergency department (ED), but the transposition of published data to routine emergency practice is sometimes limited. An observational retrospective study was conducted in the adult ED of the Reims University Hospital (France). Over one year, 852 patients suspected of infection were included, of mean age 61.7 years (SD: 22.6), and 624 (73.2%) were hospitalized following ED visit. Overall, 82 (9.6%) patients died during their hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
1
0
7
Order By: Relevance
“…Nueve se desarrollaron en España [ 37 , 39 , 40 , 43 , 44 , 46 , 48 , 49 , 53 ], siete en otros países europeos [ 36 , 41 , 45 , 50 , 51 , 52 , 54 ] y tres en Asia [ 38 , 42 , 47 ]. En total se han incluido 18.120 pacientes con 2.877 bacteriemias verdaderas (15,88 %).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Nueve se desarrollaron en España [ 37 , 39 , 40 , 43 , 44 , 46 , 48 , 49 , 53 ], siete en otros países europeos [ 36 , 41 , 45 , 50 , 51 , 52 , 54 ] y tres en Asia [ 38 , 42 , 47 ]. En total se han incluido 18.120 pacientes con 2.877 bacteriemias verdaderas (15,88 %).…”
Section: Resultsunclassified
“…En la tabla 2 se muestra la evaluación de la calidad de los estudios de cohortes incluidos y de sus riesgos de sesgos según la escala NOS [ 34 ]: 9 de ellos fueron calificados de calidad alta (bajo riesgo de sesgos) [ 26 , 36 , 37 , 39 , 40 , 41 , 43 , 49 , 50 ], 9 moderada [ 38 , 42 , 44 , 45 , 46 , 47 , 48 , 52 , 53 ] y 1 baja (alto riesgo de sesgos) [ 51 ]. Para los estudios incluidos y agrupados de la revisión sistemática [ 24 ] se asumió el análisis publicado en la misma que utilizó para la evaluación de la calidad la herramienta Quality Assessment of Diagnostic Accuracy Studies (QUADAS) [ 71 ], cuyas puntuaciones oscilan entre 0 y 14, para evaluar la calidad metodológica de los estudios incluidos.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A similar trend was reflected in the IL-10 level of the G-group. Some studies have shown that PCT can be used as an indicator of infectious diseases, infection severity and disease prognosis (32)(33)(34). However, a single PCT has some limitations, and other indicators often need to be combined in clinical practice (35).…”
Section: Discussionmentioning
confidence: 99%